Evaluation of positions of four lingula shapes for mandibular ramus surgery - Hsu, Kun-Jung; Chen, Pei-Jung; Chen, Han-Sheng; Lee, Kun-Tsung; Chen, Chun-Ming (Frontiers in Oral Health, 2025)
BackgroundThe lingula is an important landmark for conducting certain mandibular surgery procedures, such as sagittal split ramus osteotomy (SSRO) and intraoral vertical ramus osteotomy (IVRO). The purpose of this study was to investigate the location of the lingula in both horizontal and vertical planes among four different shapes of the mandibular ramus.MethodsNinety patients, 60 female and 30 male, underwent cone beam computed tomography scans to evaluate the measurements of the lingula tip (Li) in relation to the anterior border (AB), posterior border (PB), sigmoid notch (SN), and inferior border (IB) of the ramus. The proportional relationship of the Li in both the horizontal and vertical planes is indicated by the Li–AB/AB–PB ratio and Li–SN/SN–IB. lingula shapes were categorized into triangular, truncated, nodular, and assimilated shapes. Statistical analyses were performed to compare the variations in the measurements between different shapes of lingula and genders.ResultsThe mean Li–AB distance was 18.88 mm, and it was determined to be significantly greater with the truncated shape when compared to the other three shapes. The mean Li–PB distance was 15.23 mm, with no significant differences observed among the four shapes. The mean Li–AB/AB–PB ratio was found to be 55.3%. The truncated shape had a ratio of 57.2%, which was significantly higher compared to the nodular shape (54%) and assimilated shape (50.4%). The mean distance was 19.95 mm for the Li–SN and 31.34 mm for the Li–IB. There was no significant difference in these distances among the 4 lingula shapes. The mean Li–SN/SN–IB ratio was 38.5%. There were no significant differences in measurements between male and female.ConclusionSignificant differences were observed in the 4 lingula shapes in relation to the Li position, which was situated superiorly and posteriorly to the central point of the ramus. Therefore, it is crucial to take into account the differences in lingula shapes during SSRO and IVRO procedures on the ramus.